ANALISIS PERANCANGAN SISTEM INFORMASI PENGADUAN MAHASISWA DI FTI UNTAR MENGGUNAKAN PENDEKATAN UML - Owen Maytrio Phratama; Teny Handhayani; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The process of delivering student aspirations and complaints is one of the important aspects in enhancing the quality of education in higher education. One of them is the Faculty of Information Technology, Tarumanagara University, which is committed to providing high-quality academic and non-academic services. The current process of submitting aspirations and complaints is done manually because there is no centralized platform to collect complaint data, causing the handling of complaints to be hampered and less efficient. This research aims to analyze the design of a web-based student complaint information system in the FTI Untar environment to facilitate students in conveying aspirations and complaints. From the faculty side, this system also makes it easier to collect data on aspirations and complaints so they can respond to complaints more efficiently so as to improve the quality of education at FTI Untar. Data was gathered through a review of literature and interviews with FTI Untar stakeholders to collect and analyze user needs. System design analysis was conducted using UML (Unified Modeling Language) to visualize, design, and document various aspects of the system by describing use case diagrams, activity diagrams, class diagrams, and sequence diagrams, which help map workflows, main functions, and relationships between system components comprehensively.